2000
DOI: 10.1046/j.1442-200x.2000.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Preperitoneal fat thickness in childhood obesity: Association with serum insulin concentration

Abstract: These results indicate the important contribution of visceral fat accumulation to the development of hyperinsulinemia, regardless of sex. Accordingly, it is suggested that evaluating Pmax by ultrasonography may be the most sensitive and reliable method of predicting insulin resistance-associated metabolic derangements in children, compared with other conventional indices of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 22 publications
2
23
0
2
Order By: Relevance
“…Pmax and Smin were measured directly from the screen with electronic calipers. Pmax and Smin were both related with visceral fat accumulation and subcutaneous fat accumulation in the upper abdomen as reported in a previous study (21).…”
Section: Anthropometric Measurementssupporting
confidence: 84%
See 1 more Smart Citation
“…Pmax and Smin were measured directly from the screen with electronic calipers. Pmax and Smin were both related with visceral fat accumulation and subcutaneous fat accumulation in the upper abdomen as reported in a previous study (21).…”
Section: Anthropometric Measurementssupporting
confidence: 84%
“…On the other hand, serum adiponectin levels were not correlated with POW, PBF or Smin. Waist circumference and Pmax were related with visceral fat accumulation, and Smin was related with subcutaneous fat accumulation as reported in previous studies (21,24). Nishina et al revealed a significant relationship between visceral fat accumulation and insulin in obese Japanese children (25).…”
Section: Discussionsupporting
confidence: 68%
“…[33][34][35][36][37][38][39] Thus, the main prognostic problem in obesity is to estimate accurately the quantity and distribution of fat in the body. Both CT and MRI have been used in children and adolescents for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…The probe was applied lightly to the skin in order to avoid compression of the fat layer. Maximum preperitoneal fat thickness (Pmax) and minimum subcutaneous fat thickness (Smin) were measured directly from the screen using electronic calipers (16). Birth weight and gestational weeks were obtained from maternal and child health handbooks.…”
Section: Methodsmentioning
confidence: 99%